Socio-Educational Work in Social Service in Gramscian thinking: the Organic Intellectual - Adriana Giaqueto Jacinto (Revista Katálysis, 2017)
This essay addresses the contribution of Gramscian thinking to social service using as a reference the apprehension of the relations between politics and culture, with an emphasis on the educational dimension of the work of social assistants. The central questioning is: can social assistants, as professionals who work with the class that has been expropriated of its basic rights, assume the role of organic intellectuals, in the Gramscian concept? It uses the history of the life and work of Gramsci to situate the concept of the organic intellectual and his relationship with other contents imbricated in the theme of politics and culture, reflecting on the expansion of the understanding of pedagogical practice, grasping it in the broad process of the class struggles, linked to the issue of hegemony.